2022
DOI: 10.3390/ijms23031336
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Bacterial DNA Extraction Method to Explore the Urinary Microbiota

Abstract: Recent advances in molecular biology have been successfully applied to the exploration of microbiota from various fluids. However, the urinary microbiota remains poorly explored, as its analysis requires specific technical considerations. Indeed, urine is a low microbial biomass environment, in which the representativity of each bacterium must be respected to obtain accurate data. Thus, sensitive extraction methods must be used to obtain good quality DNA while preserving the proportions between species. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Hence, sufficient DNA was extracted from the spiked samples for the sequencing steps within 35 minutes. Previous studies have also reported that the Blood and Tissue kit is best for DNA isolation from artificial human urine samples and canine urine (41,42). Karstens et al (43) also reported higher DNA yield from human urine by the Blood and Tissue kit, although DNA produced by both BiOstic and Blood and Tissue kits performed well in downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, sufficient DNA was extracted from the spiked samples for the sequencing steps within 35 minutes. Previous studies have also reported that the Blood and Tissue kit is best for DNA isolation from artificial human urine samples and canine urine (41,42). Karstens et al (43) also reported higher DNA yield from human urine by the Blood and Tissue kit, although DNA produced by both BiOstic and Blood and Tissue kits performed well in downstream analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the critical steps for metagenomics-based diagnostic methods is DNA extraction, as variation in the extraction protocol can severely affect sequencing results. While studies have been carried out to determine the extraction efficiencies of different extraction kits on samples such as stool and blood, the urinary microbiome is relatively less explored (21,22). Some of the challenges encountered when working with urine samples are limited microbial biomass compared to other samples, the presence of different salt and urine components that can interfere with the extraction, and the presence of different assay inhibitors (23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PBS was discarded by centrifugation at 10,500 rpm/15 min/4°C immediately before genomic extraction. Genomic DNA from urine samples was extracted using the Qiagen DNeasy blood and tissue kit (Qiagen, Germany) according to the manufacturer’s protocol, using pretreatment for Gram-negative bacteria ( 51 ). DNA was eluted into 50 μL of Tris-HCl (pH 8.0) and stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it is important to critically evaluate and identify gaps in current benchmarking and optimization studies for pediatric urobiome applications. For example, many of the laboratory methods have been evaluated for optimization on adult human and canine urines ( 88 90 ), and several comparisons of detection methods ( 91 ), and bioinformatics ( 38 , 41 ) specifically for the urobiome. It is also essential that investigators in the pediatric urobiome research community employ current recommendations developed by the urobiome ( 15 ), kidney microbiome ( 92 ), and general microbiome communities ( 93 ) and develop consensus on standards and guidelines for the field.…”
Section: Larger Gaps To Be Addressed In Future Studiesmentioning
confidence: 99%